More on the Borwein-Ditor Theorem - Miller, Harry I.; Miller-Van Wieren, Leila (Sarajevo Journal of Mathematics, 2024)
In 1978 D. Borwein and S. Z. Ditor published a paper answering a question of P. Erdos. Since then several authors including N. Bingham, P. Komjath, H. Miller, L. Miller-Van Wieren, A. Ostaszewski have generalized and extended their result. In this paper a significant generalization of all previous results is presented. 2000 Mathematics Subject Classification. 40D25, 40G99, 28A12